Di sản làng nghề xứ Thanh với phát triển du lịch : Sách chuyên khảo / Nguyễn Thị Thục, Nguyễn Thị Lan Hương chủ biên, Nguyễn Đức Thắng... - Nguyễn, Thị Trúc QuỳnhTS.
Thư mục: tr. 327-336. - Phụ lục: tr. 337-370